Relationships between stem CO(2) efflux, substrate supply, and growth in young loblolly pine trees - Maier, Chris A (The New phytologist, 2010)
*We examined the relationships between stem CO(2) efflux (E(s)), diameter growth, and nonstructural carbohydrate concentration in loblolly pine trees. Carbohydrate supply was altered via stem girdling during rapid stem growth in the spring and after growth had ceased in the autumn. We hypothesized that substrate type and availability control the seasonal variation and temperature sensitivity of E(s). *The E(s) increased and decreased above and below the girdle, respectively, within 24 h of treatment. Seasonal variation in E(s) response to girdling corresponded to changes in stem soluble sugar and starch concentration. Relative to nongirdled trees, E(s) increased 94% above the girdle and decreased 50% below in the autumn compared with a 60% and 20% response at similar positions in the spring. *The sensitivity of E(s) to temperature decreased below the girdle in the autumn and spring and increased above the girdle but only in the autumn. Temperature-corrected E(s) was linearly related to soluble sugar (R(2) = 0.57) and starch (R(2) = 0.62) concentration. *We conclude that carbohydrate supply, primarily recently fixed photosynthate, strongly influences E(s) in Pinus taeda stems. Carbohydrate availability effects on E(s) obviate the utility of applying short-term temperature response functions across seasons